Synthesis of mesoporous silicas and organosilicas under mild reaction medium - Yang, Q.; Liu, Jian (Research Signpost, 2010)
Mesoporous silicas have shown potential applications in catalysis, adsorption, separation and biotechnology. Recent years have witnessed rapid growth in the area of mesoporous silicas. Mesoporous silicas and organosilicas with various structures and morphologies are synthesized based on the self-assembly of surfactant and inorganic precursors and covered by several excellent reviews. However, in most cases, mesoporous silicas were synthesized under harsh (acidic or basic) conditions. A mild synthesis approach for mesoporous silicas has attracted much research attention not only for their potential applications, but also for the fundamental understanding of the synthesis mechanism related to mesostructured silicas. This short review highlights the recent developments in the biomimetic synthesis of mesoporous silicas with hierarchical structure and morphology at different length scales, for example, mesoporous hollow spheres, mesoporous nanotubes and nanofibers, silicas supra-vesicles, as well as the recent progress in the fabrication of mesoporous organosilicas under neutral or weak acidic medium, for example, the salt induced phase transformation of mesoporous ethane-silicas in neutral medium, the organosilicas with 2-D hexagonal phase, vesicle and foam mesostructure synthesized under mild buffer solution and hollow micro and nano spheres fabricated in almost neutral conditions.